1997
DOI: 10.1021/bi970258a
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of Low-Density Lipoprotein by Hemoglobin Stems from a Heme-Initiated Globin Radical:  Antioxidant Role of Haptoglobin

Abstract: Hemoglobin, known as a poor peroxidase, has been recently found to be a highly reactive catalyzer of low-density lipoprotein (LDL) oxidation resulting in oxidation of LDL lipids and covalent cross-linking of the LDL protein, apo B. We evaluated three possible mechanisms that may account for hemoglobin reactivity: oxidative activation by globin-dissociated hemin following its transfer to LDL; peroxidase-like reactivity of the ferryl iron active state in intact hemoglobin; and oxidation by a globin radical forme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
135
1
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(145 citation statements)
references
References 53 publications
8
135
1
1
Order By: Relevance
“…It has been suggested that globin-chain free radicals are available for localized amino acid oxidations (eg, within Hb) or radical transfer to non-Hb molecules (eg, lipoproteins). 9,10 The proposed final outcome of these reactions is Hb self-destruction, hemin loss, and globin chain cross-linking/ precipitation, which can ultimately lead to tissue damage. 11 It should be noted that the putative impact of these reactions on disease conditions is based on limited and indirect experimental evidence, so it remains uncertain whether significant quantities of Hb-Fe 4ϩ and radicals are generated during in vivo hemolysis and if they contribute to disease.…”
Section: Mechanism 2: No and Oxidant Reactionsmentioning
confidence: 99%
“…It has been suggested that globin-chain free radicals are available for localized amino acid oxidations (eg, within Hb) or radical transfer to non-Hb molecules (eg, lipoproteins). 9,10 The proposed final outcome of these reactions is Hb self-destruction, hemin loss, and globin chain cross-linking/ precipitation, which can ultimately lead to tissue damage. 11 It should be noted that the putative impact of these reactions on disease conditions is based on limited and indirect experimental evidence, so it remains uncertain whether significant quantities of Hb-Fe 4ϩ and radicals are generated during in vivo hemolysis and if they contribute to disease.…”
Section: Mechanism 2: No and Oxidant Reactionsmentioning
confidence: 99%
“…Endocytosis by macrophages results in lysosomal degradation of the protein and of the heme by heme oxygenase 1, releasing ferrous iron (Fe(II)), biliverdin, and CO [48]. Knock-out mice lacking Hp have no difficulty in clearing Hgb [49], rather the role of Hp would seem to be to protect against oxidative damage to lipids and LDL [50,51].…”
Section: Role Of Methemoglobin In Inflammationmentioning
confidence: 99%
“…Hb has been known to have a weak peroxidase activity, since it degrades H2O2 in a peroxidase-like manner, 20) but it has no catalase-like activity. 6) Other hemoproteins have properties similar to Hb, and thus studies on various hemoproteins such as myoglobin (Mb) and horseradish peroxidase (HRP) provide us with general knowledge about the redox chemistry of hemes.…”
Section: Pseudoperoxidase Cyclementioning
confidence: 99%